A limited number of species is sufficient to assign a vegetation plot to a forest vegetation unit. Issue 1 (24th March 2022) - Maciejewski, Lise; Pinto, Paulina E.; Wurpillot, Stéphanie; Drapier, Jacques; Cadet, Serge; Muller, Serge; Agou, Pierre; Renaux, Benoît; Gégout, Jean‐Claude
Abstract: Aims: Inventorying the habitats composing Natura 2000 sites is mandatory in the European Union and is necessary to implement relevant conservation measures. Vegetation plots, recording the presence or abundance of all plant species co‐occurring within a plot, are currently used to identify terrestrial Natura 2000 habitat types, whose descriptions are mainly based on phytosociological units. However, vegetation plots are time‐consuming and frequently restricted to the growing season. Moreover, no vegetation plots can be regarded as exhaustive, and significant inter‐observer variation has been highlighted. We studied whether reducing the number of recorded species and the time spent carrying out a vegetation plot had an impact on vegetation unit assignment using species presence. We also studied if vegetation plots recorded in winter could be used for vegetation unit assignment. Location: Mainland France. Methods: We used 273 vegetation plots covering French temperate and mountainous forests. The time at which species were sighted was recorded. We also estimated whether a species was recognisable in winter. We used a classification program to compare assignments based on complete and incomplete vegetation plots. Results: Ten species and five minutes were sufficient to assign a plot to an association, and to an alliance, seven species and four minutes. Vegetation unit assignment proved feasible in winter, especially at the alliance level. Conclusions: We confirmed that a limited number of species is sufficient to assign vegetation plots to vegetation units. However, mapping habitats requires habitat identification and delimitation. This study confirms current field habits, particularly when creating a habitat map, usually based on a limited number of recorded species. Lastly, it confirms that the use of vegetation plots coming from a great variety of sources is relevant to create habitat time series, crucial tools for monitoring habitats at a national scale. Abstract : A limited number of species — hence a limited field time too — is sufficient to assign a vegetation plot to a forest vegetation unit. Thus, the use of vegetation plots coming from a great variety of sources is relevant to create habitat time series that are crucial tools for monitoring habitats at a national scale.